PERAN JURNALISME PROFETIK MENGHADAPI HOAX - Dian Muhtadiah (Jurnal Dakwah Tabligh, 2017)
“Terror” hoax or information in the form of text, images, or video lying or twisting is considered to be so massive terrorizing public spaces in the network (online) in Indonesia. Start from image or text links in online social networks, such as Facebook, Twitter, Instagram to chain messages in the Whats-app group. Internet users who are not on guard with ghost terror hoax easily spread it to their colleagues in the online space so as to bring the effect of a growing snowball. The prophetic journalism offered in the Islamic press offers solutions to minimize the terror of the hoax.